Semaphorin 3A: A Potential Target for Low Back Pain - Yin, Pengbin; Lv, Houchen; Zhang, Lihai; Zhang, Licheng; Tang, Peifu (Frontiers in Aging Neuroscience, 2015)
Low back pain is a common disorder. Pathological innervation and intervertebral disc degeneration are two major factors associated with this disease. Semaphorin 3A, originally known for its potent inhibiting effect on axonal outgrowth, is recently found to correlate with disease activity and histological features in some skeletal disorders. Based on its effects on innervation and vascularization, as well as enzyme secretion, we presume that semaphorin 3A may act as a potential target for low back pain.